Vaccine Failures in Patients Properly Vaccinated with 13-Valent Pneumococcal Conjugate Vaccine in Catalonia, a Region with Low Vaccination Coverage. Issue 4 (April 2016) - Moraga-Llop, Fernando; Garcia-Garcia, Juan-Jose; Díaz-Conradi, Alvaro; Ciruela, Pilar; Martínez-Osorio, Johanna; González-Peris, Sebastià; Hernández, Sergi; de Sevilla, Mariona Fernández; Uriona, Sonia; Izquierdo, Conchita; Selva, Laura; Campins, Magda; et al.
Abstract : Vaccine failures occurring with 13-valent pneumococcal conjugate vaccine (PCV13) in 3 pediatric hospitals in Barcelona (2012–2013) are described. PCV13 vaccine failure was defined as the occurrence of an invasive pneumococcal infection in children properly vaccinated by PCV13. Among 84 patients with invasive pneumococcal infection, 32 had received at least one dose of PCV13. Seventeen of them had invasive pneumococcal infection produced by a PCV13 serotype. Among those, 9 patients were considered to have a PCV13 vaccine failure. Serotype 3 was isolated in 6 patients, serotype 19A in 2 and serotype 6B in 1.